Assessing inherent health hazard for proposed plants - H., Mimi (Penerbit UTM Press, 2003)
Proper selection of chemical process route is one of the main design decisions during the preliminary stages of chemical plant design. Previously, the most important factor for selecting the best chemical process route was only the economics. But now, safety, environmental and health issues have become important factors to be considered. Health risks on workers could also be reduced by proper selection of chemical process route. However, the health hazards needed to be quantified in order to choose the ‘healthiest’ route. Process Route Healthiness Index (PRHI) has been developed to foresee the potential health hazards from chemical processes. PRHIP ranks process routes in terms of their occupational healthiness. The higher the index, the higher is the hazard. PRHI is influenced by the health impact due to chemical releases and the concentration of airborne chemicals inhaled by workers. In this article, PRHI has been applied on six alternative routes for Methyl Methacrylate (MMA). The results of the ranking was compared to the Inherent Safety Index, Environmental Hazard Index and production costs for the six alternative chemical process routes.